Mismatch Negativity Occurrence with Verbal and Nonverbal Stimuli in Normal-Hearing Adults - Brückmann, Mirtes; Garcia, Michele Vargas (International Archives of Otorhinolaryngology, 2020)
Introduction The mismatch negativity (MMN) is a long-latency auditory evoked potential related to a passive elicited auditory event.Objective To verify the occurrence of MMN with different stimuli, to describe reference values in normal-hearing adults with verbal and nonverbal stimuli and to compare them with each other, besides analyzing the latency, area, and amplitude regarding gender and between the ears.Method Normal-hearing individuals, aged between 18 and 59 years old, participated in the study. As inclusion criterion in the study, all of them underwent tone threshold audiometry, logoaudiometry, tympanometry, and the Dichotic Sentence Identification (DSI) test, and later the MMN with 4 different stimuli, being 2 verbal (da/ta and ba/di) and 2 nonverbal stimuli (750/1,000Hz and 750/4,000Hz), which are considered stimuli with low and high contrast.Results A total of 90 individuals composed the sample, being 39 males and 51 females, with an average age of 26.9 years old. In the analysis of the latency, amplitude, and area of the four stimuli between the ears, they were not considered statistically different. There was a significant difference between all of the stimuli in terms of latency, amplitude and area, with the highest latency found in da/ta, and the greatest amplitude and area in ba/di. Regarding gender, there was only difference in the latency of the da/ta stimulus.Conclusion The da/ta and 750/1,000Hz stimuli elicited the most MMN in the population of normal-hearing adults. Among the genders, there was difference only regarding the latency of the verbal stimulus da/ta, and there was no difference between the ears.
Keywords: auditory evoked potentials; auditory cortex; hearing; adult; electrophysiology